Diseño del plan estratégico de la empresa Granja Avícola Las Tunas (2016)
The poultry farm "Las Tunas" is a business categorized as PYME, whose purpose is the production of chicken eggs for human consumption; its market is focused on wholesale customers who collect the product in their facilities because they do not have a defined distribution channel. A events and exposed are added difficulties in its organization and operation leading to missed opportunities that can provide the environment and the strengths of the company, therefore, was an urgent need for a study to the projection design a strategic plan that responds to the future success of staying in the market, increase profitability and sponsoring the growth of the company within the industry.